1997
DOI: 10.2166/wst.1997.0407
|View full text |Cite
|
Sign up to set email alerts
|

An activated sludge process without excess sludge production

Abstract: An activated sludge process which produces no excess sludge was developed. The process is very simple as a small amount of return sludge is ozonated and then returned to the aeration tank. The ozonation enhances biodegradability of activated sludge, which is biologically oxidized in the aeration tank. A full-scale plant for treating 450m3/d of municipal wastewater was constructed and has been operated successfully for 9 months. The amount of excess sludge eliminated is directly proportional to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 0 publications
1
55
1
2
Order By: Relevance
“…But the comparison and evaluation of these processes for sludge lysis is not considered in this paper. Sludge lysis and subsequently cryptic growth could be promoted by physical, chemical and combined ways in order to reduce sludge production, such as ozonation [31][32][33][34][35][36][37][38], chlorination [39,40], integration of thermal/ ultrasonic treatment and membrane [41,42], integration of alkaline and heat treatment [43][44][45], and increase of oxygen concentration [46]. Table 1 summarizes sludge reduction under lysis-cryptic growth condition.…”
Section: Lysis-cryptic Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…But the comparison and evaluation of these processes for sludge lysis is not considered in this paper. Sludge lysis and subsequently cryptic growth could be promoted by physical, chemical and combined ways in order to reduce sludge production, such as ozonation [31][32][33][34][35][36][37][38], chlorination [39,40], integration of thermal/ ultrasonic treatment and membrane [41,42], integration of alkaline and heat treatment [43][44][45], and increase of oxygen concentration [46]. Table 1 summarizes sludge reduction under lysis-cryptic growth condition.…”
Section: Lysis-cryptic Growthmentioning
confidence: 99%
“…Throughout the operation periods of full-scale plants with sludge ozonation process for treating municipal wastewater and industrial wastewater, respectively, no excess sludge was withdrawn and no significant accumulation of inorganic solids occurred in the aeration tank at optimal ozone dose rates. The operation costs of this process were estimated to be lower than those of conventional sludge treatment process, including sludge dewatering and disposal [32,33]. Different from their continuous ozonation way [31][32][33], Kamiya and Hirotsuji [34] therefore developed a new system combining both biological treatment and intermittent ozonation to reduce the excess sludge production with fewer amounts of ozone and simultaneously control the sludge bulking.…”
Section: Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…model by removing irrelevant points from the structure of prior parameters under the framework of Bayesian. Compared with support vector machine (SVM), relevance vector machine(RVM) has the following advantages: (1) subjective setting error parameters is avoided; (2) the relevant vector is less than the SVM; (3) kernel function need not meet the Mercer condition, resulting in a greater range of options 7 . For a given data set { }…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of ozone to reduce excess sludge has drawn wide attention (Liu and Tay, 2001). Sakai et al (1997) carried out a full-scale experiment on ozonation of the sludge and found that excess sludge was reduced by 66%. The sludge reduction rate reported by Bohler and Siegrist (2004) was 46%.…”
Section: Introductionmentioning
confidence: 99%